Sensors in special purpose technical assets - Milanović, Zoran; Milić, Saša; Radovanovic, Radovan (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Special-purpose technical assets for measurement and monitoring are being rapidly developed with the goal of improving sustainable security and electronic protection of people and objects. This paper, in a broader sense, gives a general division and application of intelligent infrared sensors in the technical assets of the army and police, while in a narrower sense it gives a metrological overview of smart measuring sensors, devices and systems, and ways and areas of their application. In a narrower sense, the paper analyses and show in detail the systems that use thermal imaging cameras. A series of examples are given from world practice with the aim of illustrating and confirming the importance of the application of measuring and monitoring IC systems.